How does social media marketing impact consumer response? The role of brand equity in Indonesia’s SVOD Services - Giovany Tarminasyah Nainggolan; Inggang Perwangsa Nuralam (Faculty of Economics and Business, University of Muhammadiyah Malang, 2026)
The growth of digital technology has led Indonesians to increasingly use social media, a trend that marketers leverage to enhance brand awareness, image, loyalty, and willingness to pay premium prices. This study examines the impact of Social Media Marketing Activities on Brand Loyalty and Willingness to Pay Premium Prices, with Brand Awareness and Brand Image as intervening. Using the Stimulus-Organism-Response (S-O-R) framework, social media marketing activities as the stimulus, brand equity (awareness and image) as the organism, and consumer responses (loyalty and willingness to pay premium) as the response. Data was collected from 270 Indonesian Subscription Video-on-Demand users through purposive sampling and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) via SmartPLS. Results indicate that social media marketing activities significantly influences brand awareness and brand image, which, in turn, significantly impact brand loyalty and the willingness to pay premium prices